ProtectionoOf Victims Affected by Default Umrah Tour and Travel: In Terms of Law no. 8 Of 1999 Concerning Consumer Protection - Budiawan, Taufik; Herman, KMS.; Hidayati, Hidayati (Blantika: Multidisciplinary Journal, 2024)
Today's rapidly growing travel business requires a travel agency to help take care of administration and paperwork to enter other countries. Travel agencies provide these services with a variety of attractive advertisements. This purpose of the study is to provide awareness to the public to choose Umrah Tours and Trips that have a track record that can be accounted for and provide consumer protection for victims in order to reach mutually beneficial agreements. The methods used are in the regulatory process using primary and additional legal data. Following the investigation, Law no. 8 of 1999 for the protection of consumers was promulgated for the victims of default due to Umra Tour and Travel's failure to comply with the terms and conditions of the contract provided to consumers. In some cases, travel agencies will obtain legal proceedings and provide compensation or compensation if they do not provide disruption in accordance with the promised services This research can also help determine legal protection for consumers, for example in some cases, for example a breach of contract by a travel agent can be considered a violation of business law and can be penalized.